Intensified partner notification and repeat testing can improve the effectiveness of screening in reducing Chlamydia trachomatis prevalence: a mathematical modelling study. (23rd November 2021) - Hui, Ben B; Hocking, Jane S; Braat, Sabine; Donovan, Basil; Fairley, Christopher K; Guy, Rebecca; Spark, Simone; Yeung, Anna; Low, Nicola; Regan, David
Abstract : Background: The Australian Chlamydia Control Effectiveness Pilot (ACCEPt) was a cluster randomised controlled trial designed to assess the effectiveness of annual chlamydia testing through general practice in Australia. The trial showed that testing rates increased among sexually active men and women aged 16–29 years, but after 3 years the estimated chlamydia prevalence did not differ between intervention and control communities. We developed a mathematical model to estimate the potential longer-term impact of chlamydia testing on prevalence in the general population. Methods: We developed an individual-based model to simulate the transmission of Chlamydia trachomatis in a heterosexual population, calibrated to ACCEPt data. A proportion of the modelled population were tested for chlamydia and treated annually at coverage achieved in the control and intervention arms of ACCEPt. We estimated the reduction in chlamydia prevalence achieved by increasing retesting and by treating the partners of infected individuals up to 9 years after introduction of the intervention. Results: Increasing the testing coverage in the general Australian heterosexual population to the level achieved in the ACCEPt intervention arm resulted in reduction in the population-level prevalence of chlamydia from 4.6% to 2.7% in those aged 16–29 years old after 10 years (a relative reduction of 41%). The prevalence reduces to 2.2% if the proportion retested within 4 months of treatment is doubled from the rate achieved in the ACCEPt intervention arm (a relative reduction of 52%), and to 1.9% if the partner treatment rate is increased from 30%, as assumed in the base case, to 50% (a relative reduction of 59%). Conclusion: A reduction in C. trachomatis prevalence could be achieved if the level of testing as observed in the ACCEPt intervention arm can be maintained at a population level. More substantial reductions can be achieved with intensified case management comprising retesting of those treated and treatment of partners of infected individuals.